FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL STUDI EMPIRIS PADA PERUSAHAAN YANG LISTING DI JAKARTA ISLAMIC INDEX 2012-2014 - Setyaningsih, Ratih Nur; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2016)
In the „knowledge based business‟ paradigm, intellectual capital have become a pre-eminent economic resources and the basis for competitive advantages. The main objective of this study was to examine factors - factors that affect the disclosure of intellectual capital in the companies listed in Jakarta Islamic Index (JII) in 2012 - 2014. The variables used are the Intellectual Capital Disclosure Item, Firm Age, Firm Size, Leverage, Profitability, Level of Intellectual Capital, and the type of Auditors. Measurement of intellectual capital items using models of Bukh et al. 2005, namely employees, customers, information technology, processes, and reporting strategies. This study indicates that the voluntary disclosure of intellectual capital finding suggest that the age, size, and type of auditor found to have an influence on the amount of intellectual capital disclosure. Other factors, such as leverage, profitability, and level of intellectual capital were found not to have an influence on the amount of intellectual capital disclosure. The method is applied using multiple regression analysis, the statistical test of hypothesis testing and statistical test t F. The results showed that the age of the firm and the size, has a significant influence on the intellectual capital disclosure. Type of auditor have an influence on the amount of intellectual capital disclosure. However, this study did not find a positive effect on leverage, profitability and level of intellectual capital on the disclosure of intellectual capital